Aplikasi Whatsapp Pelacak Berbasis Arduino (Dunod Kertasapp) - Reksaka Fati Phonna; Eka Rosita; Kintan Utari; Irnin Agustina Dwi Astuti; Iman Noor (UNIVERSITAS INDRAPRASTA PGRI, 2020)
A research of an Arduino based tracker Whatsapp has been performed (Dunod Kertasapp). This research aims to make instrumental tracker from Whatsapp application with Arduino. Through a simple experiment, we got tracking a vehicle position with the distance between 500 meter until 1000 meter from main position.